Propuesta de creación de un centro de desarrollo educativo y tareas dirigidas para los hijos de los trabajadores del mercado Las Cuadras en la parroquia de Chillogallo - Cabascango Quilumba, Edison David (2015)
This degree work focuses on the career of Business Administration, a project that is based on the proposed establishment of a center for educational development and targeted for children of market workers stables in the parish of Chillogallo tasks. This book seeks to improve the educational and social reality of living children of traders association Mariscal Sucre daily; through the study shows that the existing population in the sector belongs to a middle socio-economic strata bass with notable educational and family problems mostly. The surveys show that children are about three hundred children in a position to benefit from the center; the same in the first instance will be covered for 120 infants and substantiate on three pillars of development such as educational support; counseling and business training. The existing provision in the area with similar characteristics proposed topic is scarce leaving a considerable unmet demand. The technical study denotes the physical structure; equipment, supplies and human capital necessary to carry out the proposed theme. So essential goods and services as their prices resulting in fixed and working capital required to finance the realization study presented detailed investment. As a project purely social order and collective development include the impact factors that produce the institution in the contextual environment in which it operates